DEVELOPMENT STRATEGY COVID-19 SCREENING AT MARDI WALUYO BLITAR HOSPITAL - Ratna Wardani; Devita Riafinola; Novi Kurniasari; amalianurzahra; Tutus Fibri; Agus Wahyudi (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
ABSTRACT WHO announced Covid-19 as pandemic on 11th March 2021. In order to prevent the spread of Covid-19, Mardi Waluyo Hospital has an application for online screening that can be accessed independently by patients. This application will make patients and health workers easier and accelerate the health services. The aim of community dedication program that held in RSUD Mardi Waluyo is develops an online covid-19 screening system and provides education so that both health workers and the community able to use application of online covid-19 screening to reduce direct contact between health workers and patients. At the initial stage, socialization was given to health workers starting from management, registration, program and staffing division, head of nursing, head of medical support, public relations, nurses, and medical records. To introduce the online screening application, socialization is carried out directly and through the media. An understanding of the online screening application is important because we can measure how successful the online screening implementation plan at Mardi Waluyo Hospital. Before socialization, understanding about online screening applications was 56.00, while after socialization was 91.00. It shows that there is an increase in participants' understanding after the socialization. Keywords: Covid-19, Online Screening, Socialization